Pricing and Financial Resources: An Analysis of the Disk Drive Industry, 1980-88 - Lerner, Josh (The Review of Economics and Statistics, 1995)
This paper empirically examines the 'long purse' hypothesis, formalized by Patrick Bolton and David Scharfstein (1990), that incumbents may drive out entrants through aggressive pricing. The author analyzes the pricing of 733 disk drives between 1980 and 1988. Drives that are adjacent to those manufactured by thinly capitalized undiversified rivals are priced lower than other drives during the later years in the sample, when little equity financing was available to these firms. The results are robust to controls for alternative hypotheses and to other specifications of the hedonic regression. Copyright 1995 by MIT Press.